Ketidaklangsungan Ekspresi dalam JuduI Cerita Rubrik “Nah ini Dia” Harian Pos Kota - Andi Hallang Lewa; Budi Santoso (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
Indirrect expression is widely used in writing news on the mass media, including short stories in newspapers. This paper tries to describe indirrect expressions in the title of the storiy on Poskota daily’s Column